Effect of Fe2O3 content on the electrical resistivity of aluminous porcelain applied to electrical insulators. Issue 4 (March 2016) - Piva, D.H.; Piva, R.H.; Venturini, J.; Ramon, J.; Caldas, V.; Morelli, M.R.; Bergmann, C.P.
Abstract: In general, the presence of Fe2 O3 is claimed to reduce the insulating behavior of electrical porcelains, even if a rigorous proof has not yet been reported. The purpose of this study was to evaluate the real influence of Fe2 O3 content on the electrical resistivity of a standard aluminous porcelain widely used in insulators. The electrical resistivity for the composition with 3 wt% Fe2 O3 was higher than those found for standard aluminous porcelain, which was discussed in terms of the concentration of glassy and mullite phases. A reduction in the electrical resistivity was only observed in porcelain samples containing over 3 wt% Fe2 O3 . The presence of hematite phase was considered responsible for this reduction. These results suggest that low-cost raw materials with greater Fe2 O3 content should not extensively affect the insulating properties and could therefore be used in manufacturing aluminous electrical porcelain.